Editorial: What we Need to Know About Mu, a New Variant of SARS-CoV-2 - Hassan, Taimoor (International Journal of Pathology, 2022)
Mu (B.1.621) was identified as a new SARS-CoV- 2 variant of interest by the WHO on August 30, 2021 as variant of interest (VOI). The Mu variant is found inless than 0.3% of people in the United States and less than 0.1% of people worldwide. Preliminary laboratory studies indicate that the Mu strain includesgenetic changes or "mutations" that may make it more resistant to vaccination and past infection-induced immunity. More study, however, is needed to validate these findings.1 Numerous viruses, including SARS-CoV-2, which causes COVID-19, develop through mutation over time. A viral variant has one or more genetic changes, known as mutations, that affect how the virus behaves and distinguish it from other variants. During the outbreak, several SARS-CoV-2 mutations spread throughout the United States and the rest of the world. The WHO and the Centers for Disease Control and Prevention (CDC) frequently track these changes through laboratory and epidemiological studies, as well as sequence-based surveillance. In an interview with Medical News Today, Dr. William Schaffner,M.D., professor of infectious diseases at Vanderbilt University Medical Center, claimed that "most mutations are innocuous and they go by the wayside [and] die out." Every now and then, one of these mutations evolves into an intriguing variation of interest, so we keep an eye out for it."2